2'‐Hydroxyflavanone ameliorates mesenteric angiogenesis and portal‐systemic collaterals in rats with liver fibrosis. Issue 5 (May 2016) - Hsin, I‐Fang; Lee, Jing‐Yi; Huo, Teh‐Ia; Lee, Fa‐Yauh; Huang, Hui‐Chun; Hsu, Shao‐Jung; Wang, Sun‐Sang; Ho, Hsin‐Ling; Lin, Han‐Chieh; Lee, Shou‐Dong
Abstract: Background and Aim: Portal‐systemic collaterals lead to dreadful consequences in patients with cirrhosis. Angiogenesis participates in the development of liver fibrosis, hyperdynamic circulation, and portal‐systemic collaterals. 2′‐Hydroxyflavanone (2′‐HF), one of the citrus fruits flavonoids, is known to have antiangiogenesis effect without adverse response. However, the relevant effects in liver fibrosis have not been surveyed. Methods: Male Wistar rats received thioacetamide (TAA, 100 mg/kg tiw, i.p.) for 6 weeks to induce liver fibrosis. On the 29th to 42nd day, rats randomly received 2′‐HF (100 mg/kg, qod, i.p.) or vehicle (corn oil). On the 43rd day, after hemodynamic measurements, the followings were surveyed: (i) severity of collaterals; (ii) mesenteric angiogenesis; (iii) mesenteric proangiogenic factors protein expressions; (iv) Mesenteric vascular endothelial cells apoptosis; and (v) Mesenteric expressions of proteins regulating apoptosis. Results: Compared with the vehicle group, 2′‐HF did not significantly change body weight, mean arterial pressure, heart rate, and portal pressure in TAA rats. 2′‐HF significantly alleviated the severity of collaterals, but the mesenteric phospho‐ERK, ERK, phospho‐Akt, Akt, COX1, COX2, VEGF, and VEGFR‐2 protein expressions were not altered. The apoptotic index of 2′‐HF group was significantly higher and the mesenteric protein expressions of pro‐apoptotic factors, NFkB 50, NFkB 65, Bax, phospho‐p53, 17 kD cleaved caspase 3, and 17 kD casepase 3 were up‐regulated. Conclusions: 2′‐HF does not influence the hemodynamics but alleviated the severity of collaterals in rats with liver fibrosis and early portal hypertension. This is, at least partly, attributed to enhanced apoptosis of mesenteric vascular endothelial cells.